Combinatorial ubiquitin code degrades deubiquitylation-protected substrates - Mai Morita; Miyu Takao; Honoka Tokuhisa; Ryotaro Chiba; Shota Tomomatsu; Yoshino Akizuki; Takuya Tomita; Akinori Endo; Yasushi Saeki; Yusuke Sato; Fumiaki Ohtake (Nature Communications)
Abstract Protein ubiquitylation is maintained by a dynamic balance of the conjugation and deconjugation of ubiquitin. It remains unclear how deubiquitylation-stabilized substrates are directed for degradation. Branched ubiquitin chains promote substrate degradation through the proteasome. TRIP12 and UBR5 are HECT-type E3 ubiquitin ligases, which are specific for lysine 29 (K29) and lysine 48 (K48) linkages, respectively. Here, we show that the deubiquitylase (DUB) OTUD5 is cooperatively modified by TRIP12 and UBR5, resulting in conjugation of K29/K48 branched ubiquitin chains and accelerated proteasomal degradation. TRIP12–OTUD5 antagonism regulates TNF-α–induced NF-κB signaling. Mechanistically, OTUD5 readily cleaves K48 linkages, but does not affect K29 linkages. Consequently, K29 linkages overcome OTUD5 DUB activity to facilitate UBR5-dependent K48-linked chain branching. This mechanism is applicable to other OTUD5-associated TRIP12 substrates. Thus, the combination of DUB-resistant and proteasome-targeting ubiquitin linkages promotes the degradation of deubiquitylation-protected substrates, underscoring the role of branched ubiquitin chains in shifting the ubiquitin conjugation/deconjugation equilibrium.